2022
DOI: 10.1371/journal.pone.0262937
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of PEG-induced drought stress on seed germination and seedling growth of different bread wheat (Triticum aestivum L.) genotypes

Abstract: Wheat is an important crop, used as staple food in numerous countries around the world. However, wheat productivity is low in the developing world due to several biotic and abiotic stresses, particularly drought stress. Non-availability of drought-tolerant wheat genotypes at different growth stages is the major constraint in improving wheat productivity in the developing world. Therefore, screening/developing drought-tolerant genotypes at different growth stages could improve the productivity of wheat. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
(37 reference statements)
1
28
0
Order By: Relevance
“…Researchers have used it to assess the drought resistance of crops during seedling establishment since it inhibits seed germination and development by lowering water potential, and the effect is more noticeable on shoots than on main roots. In vitro screening with PEG has been shown in several studies to be one of the most accurate procedures for selecting drought-tolerant genotypes based on germination indices [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have used it to assess the drought resistance of crops during seedling establishment since it inhibits seed germination and development by lowering water potential, and the effect is more noticeable on shoots than on main roots. In vitro screening with PEG has been shown in several studies to be one of the most accurate procedures for selecting drought-tolerant genotypes based on germination indices [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The standard method to test the osmotic effect on germination is by using different concentrations of polyethylene glycol (PEG), which mimics environmental drought conditions [ 65 , 66 , 67 , 68 ]. Germination of the two species proved to be tolerant to osmotic stress, no significant differences were obtained with respect to the control up to the highest PEG concentration in E. bonariensis where 92% of the seeds and in E. sumatrensis 60% of the seeds germinated, a considerably lower reduction than under NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors, especially drought stress, can affect seed germination and seedling growth in such a way that activation of enzymes can be prevented in the germination stage, and plant life cycle can be disrupted in this sensitive stage (Rezayian et al, 2018;Kour et al, 2019;Mahpara et al, 2022). Different studies have shown that drought stress impacts the seed germination of various plants (Naseem et al, 2018;Khan and Bano, 2019;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%